Grain Quality Improvement in Japonica Rice : Achievements and Prospects - Kwang-Ho Kim (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2009)
Several high grain quality rice varieties have been developed during the 2000's. These varieties showed translucent, zero white-core, glossy and uniform milled-grain appearance, high palatability score of cooked rice and high percentage of whole grain after milling. The high eating quality variety group was lower in protein content, softer in gel consistency, and higher in breakdown and lower in consistency and setback viscosity measured by rapid visco-amylogram. In order to produce the low protein rice grain, the nitrogen fertilizer level has to be reduced to 90-110 kg per hectare with no nitrogen top dressing after heading. Rotational irrigation during rice growing season and delayed drainage after heading was found as effective in raising the whole grain yield and eating quality of cooked rice. Slow drying to 15-16% of grain moisture is recommended with air flow temperature below 50oC. Three hundred and ninety four native rice core collections were tested for their grain appearance, eating quality determining factors, and nutritional compounds. Health- enhancing potential and second metabolite contents were also evaluated. The native collections selected for high grain quality resources were used as cross parents and two new rice varieties having dark red pericarp color were developed from the crosses using Korean native varieties. The new variety had higher phenolic compounds in brown rice and the brown rice extract of this variety induced apoptotic cell deaths in H4II cells to a larger extent than the control rice extracts.    Key words: rice, grain quality, variety improvement, native variety, red pericarp